Shape tailoring to enhance and tune the properties of graphene nanomechanical resonators. (22nd May 2017) - Miller, David; Alemán, Benjamín
Abstract: The shape of a nanomechanical resonator profoundly affects its mechanical properties and determines its suitability for various applications, such as ultra-sensitive mass and force detection. Despite the promise of 2D nanomechanical systems in such applications, full control over the shape of suspended 2D materials, such as graphene, has not been achieved. We present an effective, single-step method to shape pre-suspended graphene into nanomechanical resonators with arbitrary geometries leading to enhanced properties in comparison to conventional drumheads. Our technique employs focused ion beam milling and achieves feature sizes ranging from a few tens of nanometers to several microns, while obtaining near perfect yield. We compare the mechanical properties of the shaped devices to unmodified drumheads, and find that low-tension, singly-clamped graphene cantilevers display a 20 fold increase in the mechanical quality factor ( Q ) with a factor 100 reduction in the mechanical damping. Importantly, we achieve these results while simultaneously removing mass, which enables state-of-the-art force sensitivity for a graphene mechanical resonator at room temperature. Our approach opens up a unique, currently inaccessible regime in graphene nanomechanics, one characterized by low strain, low frequency, small mass, and high Q, and facilitates tailoring of non-linearity and damping in mechanical structures composed of graphene and other 2D crystals.